Mindfulness‐based interventions for obesity‐related eating behaviours: a literature review. Issue 6 (18th March 2014) - O'Reilly, G. A.; Cook, L.; Spruijt‐Metz, D.; Black, D. S.
Summary Mindfulness‐based interventions (MBIs) targeting eating behaviours have gained popularity in recent years. A literature review was conducted to determine the effectiveness of MBIs for treating obesity‐related eating behaviours, such as binge eating, emotional eating and external eating. A search protocol was conducted using the online databases Google Scholar, PubMed, PsycINFO and Ovid Healthstar. Papers were required to meet the following criteria to be included in this review: (i) describe a MBI or the use of mindfulness exercises as part of an intervention; (ii) include at least one obesity‐related eating behaviour as an outcome; (iii) include quantitative outcomes; and (iv) be published in English in a peer‐reviewed journal. A total of N = 21 papers were included in this review. Interventions used a variety of approaches to implement mindfulness training, including combined mindfulness and cognitive behavioural therapies, mindfulness‐based stress reduction, acceptance‐based therapies, mindful eating programmes, and combinations of mindfulness exercises. Targeted eating behaviour outcomes included binge eating, emotional eating, external eating and dietary intake. Eighteen (86%) of the reviewed studies reported improvements in the targeted eating behaviours. Overall, the results of this first review on the topic support the efficacy of MBIs for changing obesity‐related eating behaviours, specifically binge eating, emotional eating and external eating.